A study to assess the efficacy of medical nutritional therapy in reducing blood sugar level in type 2 diabetic patients - Arshad, Shoaib; Khan, Amreen; Melwani, Veena; Sethia, Soumitra; Priya, Angelin; Melwani, Satish (International Journal Of Community Medicine And Public Health, 2018)
Background: Physicians in India have less time for Diet consultation, despite the fact that diet planning plays an important role in management of diabetes mellitus type II. Medical nutritional therapy is defined as Nutritional diagnostic therapy, and counseling services for the purpose of disease management. The objective of the study was to study the efficacy of medical nutrition therapy in type 2 diabetics. Methods: A study was done on residents of Fatehgarh and Shaheed Nagar area of Bhopal. 44 patients with known history of diabetes with age 45 years or above were selected by house to house visit using purposive sampling. Subjects were divided in 2 groups. 1. Intervention group- known cases of diabetes mellitus type 2 with medical nutritional therapy. 2. Non Intervention group- known cases of diabetes mellitus type 2 without medical nutritional therapy. Diet plan according to the calorie requirement on the basis of the desired body weight was prepared and prescribed to the subjects of group 1. Monthly home visits for blood glucose monitoring was done. Results: The mean RBS of group 1 was 200mg and of group 2 was 194. The mean RBS of group 1 decreased by 6.5% in second reading and 8.2% in third reading. Conclusions: Only 19 out of 22 Diabetics belonging to intervention group adhered to the prescribed medical nutrition therapy. The reason being poor patient compliance because of casual attitude towards health. Better results could be obtained if the study duration was longer and HbA1c was considered.